واقع الخصائص الريادية لدي القيادات الأكاديمية بجامعة بنغازي دراسة ميدانية تشمل عمداء ووكلاء الشؤون العلمية بالكليات بمدينة بنغازي - بوخريص السنوسي سليمان (Scientific Journal of University of Benghazi, 2021)
The aim of the study was to identify the reality of the leading characteristics of the academic leadership at the University of Benghazi. To achieve the objectives of the study, the descriptive approach was followed using the comprehensive survey method, and resolution was used as a tool for data collection and the statistical analysis program (SPSS) for analysis. The study produced a number of findings, the most important of which was the provision of leadership by academic leaders at the University level (very high), with behavioral characteristics in first place, followed by personal characteristics, and administrative characteristics. The study also showed that academic leaders at the University face a range of constraints, the most important of which are weak political and economic stability, as well as the lack of state-of-the-art technology that can help them carry out their tasks effectively. Finally, on the basis of its findings, the study presented a set of recommendations that it is hoped will be applied to strengthen the leadership of the Academy at the University of Benghazi and to reduce their constraints.